La gestión administrativa y su incidencia en el desarrollo organizacional de la librería Éxito de la ciudad de Riobamba. - Contento Salazar, Jefferson Andres (2023)
Exito bookstore in Riobamba city has carried out its activities generationally and managerial, that is, the activities are carried out as their successors did, however, after conducting an exhaustive internal and external analysis of the organization, it is noticeable that there are some flaws and omissions in the development of the managerial and organizational activities that have an impact on the development of the activities. The main objective of this research was to evaluate the impact of administrative management on the organizational development of the company; thus, factors and traits that best characterize such management and direct the company´s growth through the proper and efficient completion of its tasks were identified. The linear growth of each department of a company plays a primary role in organizational development so strategies were formulated that improve these activities and address the other shortcomings that may arise within the daily life of the organization. The hypothetical-deductive method was used, which made possible to clearly identify the problems of the study, validate the hypotheses, and formulate strategies for improving the administrative management of Éxito bookstore and that can also develop the activities efficiently and effectively within the company. With this research was possible to establish the organizational problem and identify the factors, characteristics, and causes that may contribute to it. These findings also make it possible to mitigate, minimize, and eliminate the problems in question so that the business can carry out its operations normally and improve its internal comunication systems.